IMPLEMENTASI MANAJEMEN BERBASIS MADRASAH DALAM MENINGKATKAN PARTISIPASI WALI MURID DI MAN 12 JAKARTA BARAT - Paiman, Paiman; Luthfi, M. (Yayasan Education and Social Center, 2025)
This study aims to examine the implementation of School-Based Management (SBM) and its impact on parental participation at MAN 12 West Jakarta. A qualitative descriptive approach was employed to gain an in-depth understanding of the management process and parental involvement. Data were collected through in-depth interviews, participatory observation, and documentation. The results show that SBM has been well implemented, particularly in participatory planning that actively involves parents in policy formulation. However, parental participation in the management implementation and supervision stages still requires improvement due to time constraints and suboptimal communication. The school committee plays a crucial role as a mediator between the school and parents, but direct parental involvement remains limited. Digital communication media have helped enhance interactions but have not reached all parents equally. This study concludes that SBM at MAN 12 West Jakarta effectively promotes parental participation, yet more inclusive communication and empowerment strategies are needed to increase parental engagement in all aspects of school management. The findings contribute valuable insights for developing participatory and community-based educational management in madrasahs.